The Effect of Special Exercises According to the Phosphate Energy System in Developing the Rapid Ability to the Weapon Arm and the Accuracy of the Epee Attack for Girls Players - Hussein Manati Sajit (Journal of Global Pharma Technology, 2018)
The current study is of great importance as the aim of the research is to prepare phosphate-strength exercises to develop the rapid ability of the weapon arm and the accuracy of the epee attack for girls' players. Learn about the impact of exercises with phosphate effort to develop the rapid ability of the weapon arm and the accuracy of the epee attack for girls' players. The researchers use the experimental method - the two equal groups a pretest and posttest to the nature of the suitability of the study. Select the research community for girls players in the Alfahtat club in Baghdad to the fencing, totaling (20) player, as it has been selected (16) player and (80%) of the total research community as it has been divided into two groups (Control and experimental) and each group (8) players. In order to achieve the same conditions in the training modules and thus control the search variable, the two groups were trained together as a single group, in all parts of the training unit and under the direct supervision of the researcher, with the exception of the main section of the unit, the players are distributed to their groups, so that the experimental group undergoes these exercises prepared by the researchers, while the control remains on the same exercises given by the coach them. The training program took (6) weeks by (3) training units in the week a total of (18) training units, ranging training unit time (90 minutes), the duration of the proposed exercises by researchers range (30-35) minutes from the main section of the training unit time, in the exercise design, the researchers adopted a repetitive training method (90-95%) of the maximum intensity of the player. The researchers used the maximum exercise time to determine the intensity of the phosphate exercise the researchers conducted some exercises and measured the time of some player's days before the start of the main experiment and verify this during the application of his experience and exercises in the experiment so the intensity of exercise is known to researchers. One of the most important conclusions reached by the researchers is that the phosphate exercise used in research can positively affect the rapid ability of the female players in the fencing, thus positively affect the skill of accuracy of the attack and hence the proposed training exercises have achieved its proposed goals.Keywords: Special exercises, phosphate energy system, rapid ability and epee.